Creating courses for adults design for learning - St. Clair, Ralf (Jossey-Bass, 2015)
"Provides a systematic approach to lesson and course design based on research into the ways adults learn and the best ways to reach them, along with pointers and tips for teaching adults in any setting"--Provided by publisher.